Students' mathematical literacy in number pattern material seen from initial mathematical abilities - Refika Dwi Saputri; Syutaridho Syutaridho; Arvin Efriani (Fakultas Tarbiyah Universitas Ibrahimy, 2024)
Mathematical literacy ability is an individual's ability to formulate, use and interpret mathematics by reasoning, and applying concepts in various contexts. Mathematical literacy is a very important aspect for a person to have, because if someone has good mathematical literacy skills they will be able to solve problems and find solutions in everyday life. Initial mathematical abilities also have an important role in a person's ability to solve problems. The aim of this research is to describe the mathematical literacy abilities of class VIII students in terms of initial mathematical abilities.This research is a type of qualitative research with a case study research design involving 16 students in class VIII.A LTI IGM Palembang Middle School. The data collection techniques used were students' initial mathematical ability assessment scores, mathematical literacy test instruments and interviews. The research results show that students with high initial mathematical abilities are able to solve level 1, 2, 4, and 5 questions, students achieve 3 indicators of mathematical literacy, namely formulate, employ, and interpret. Students with moderate and low initial mathematical abilities are able to answer level 1, 2, and 4 questions, write conclusions correctly but without explaining the work strategy so that students are said to have not been able to achieve the formulate or employ indicators, and in the interpreting indicators students with low and medium initial abilities are the same. never been able to answer the problem. So it can be concluded that if students are able to achieve the formulate and employ indicators well and correctly then the students will also be able to achieve the interpret indicators. On the other hand, if students cannot achieve the formulate and employ indicators well and correctly then the students will not be able to achieve the interpret indicators.